2008
DOI: 10.1001/jama.300.7.814
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Exposure and Prevalence of Type 2 Diabetes in US Adults

Abstract: ContextHigh chronic exposure to inorganic arsenic in drinking water has been related to diabetes development, but the effect of exposure to low to moderate levels of inorganic arsenic on diabetes risk is unknown. In contrast, arsenobetaine, an organic arsenic compound derived from seafood intake, is considered nontoxic.Objective To investigate the association of arsenic exposure, as measured in urine, with the prevalence of type 2 diabetes in a representative sample of US adults. Design, Setting, and Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
255
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 400 publications
(273 citation statements)
references
References 46 publications
11
255
3
Order By: Relevance
“…If ingestion of organoarsenicals produces or influences DMA, they may need to be considered in toxicological and epidemiological studies. A better understanding of the relationship between seafood intake, AsB, and DMA will also contribute to the recent debate over the merits of whether or not to statistically adjust for urinary AsB in studies of risk from arsenic exposure (Navas-Acien et al, 2008;Steinmaus et al, 2009). This population does not show, based on the FIQ, high consumption of fish (8%) or shellfish (6%).…”
Section: Discussionmentioning
confidence: 99%
“…If ingestion of organoarsenicals produces or influences DMA, they may need to be considered in toxicological and epidemiological studies. A better understanding of the relationship between seafood intake, AsB, and DMA will also contribute to the recent debate over the merits of whether or not to statistically adjust for urinary AsB in studies of risk from arsenic exposure (Navas-Acien et al, 2008;Steinmaus et al, 2009). This population does not show, based on the FIQ, high consumption of fish (8%) or shellfish (6%).…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that low levels of exposure to inorganic arsenic in drinking water may play a role in diabetes prevalence. 46 From these findings, chronic exposure to arsenic is an important risk factor for induction of diabetes mellitus in an arsenic-contaminated environment.…”
Section: Arsenicmentioning
confidence: 99%
“…Among 235 subjects with plasma ADM measured by RIA kits from Peninsula Laboratories, 15 had the measured level below the limit of detection (i.e. !4.10 pmol/l) and a level equal to the limit of detection divided by the square root of two was imputed (32). Plasma fibrinogen was measured using a Cobas Fibro instrument (Roche Diagnostics) as described previously (33).…”
Section: Measurement Of Plasma Adm and Other Biomarkersmentioning
confidence: 99%